Hoạt tính xúc tác của các chất lỏng ion trên cơ sở imidazolium trong phản ứng este hóa axit béo - Nam Bình, Phạm Thị; Thúy Hạnh, Đặng Thị; Thu Hà, Vũ Thị; Tuyên, Mai (Vietnam Journal of Chemistry, 2015)
Several imidazolium-based ionic liquids were prepared and screened as catalysts for the esterification of oleic acid with methanol. The experimental results showed that both the type of anion and the length of alkyl chain in the cation have effects on the catalytic activity of ILs. In all of the ILs investigated, 1-decyl-3-methylimidazolium hydrogen sulfate (C10mimHSO4) performed the best activity.The esterification of PFAD in the precence of C10mimHSO4 was investigated. This catalyst showed good catalytic under mild conditions, the conversion of PFAD could reach 97.82 % after the esterification was carried out at 65 oC for 4 h. Futhermore, the catalyst could be reused at least 5 times, showing good operational stability. Thus, C10mimHSO4 is a promising catalyst for conversion of high free fatty acid (FFA) feeds to biodiesel.